2022
DOI: 10.7759/cureus.26702
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine-Related Arthritis: A Descriptive Study of Case Reports on a Rare Complication

Abstract: Large-scale coronavirus disease 2019 (COVID-19) vaccination programs have been rolled out worldwide. Vaccines that are widely used globally include mRNA vaccines, adenoviral vector vaccines, and inactivated whole-virus vaccines. COVID-19 vaccines can lead to varying side effects. Among the most common of these adverse effects are pain at the injection site, fatigue, and headaches. Some side effects, however, are not very well documented, and these include joint-related adverse effects. In this review, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…However, there is no description of radiographic/MRI findings in the reported cases of arthritis. 81…”
Section: Abdominal Complicationsmentioning
confidence: 99%
“…However, there is no description of radiographic/MRI findings in the reported cases of arthritis. 81…”
Section: Abdominal Complicationsmentioning
confidence: 99%
“…We report two examples: Terracina et al reported a case of a 55-year-old man developing RA flares 12 h after the second dose [ 54 ]; Watanabe et al reported a new onset of RA in a 53-year-old male only four weeks after administration of the vaccine [ 55 ]. Again, regarding RA, there have been other reports of flares, although they are considered rare events [ 56 ]. There was a study called VACOLUP which included 696 participants and which explored flares in SLE.…”
Section: Safety Of Covid-19 Vaccines In People With Autoimmunity and ...mentioning
confidence: 99%
“…For certain individuals, imaging was considered to rule out structural anomalies or trauma and to provide a more precise pathological diagnosis. The majority of arthritis patients were treated with oral and intraarticular corticosteroids, which led to clinical remission at all follow-up sessions [63].…”
Section: Post-covid-19 Arthritismentioning
confidence: 99%